Redefining Neuropsychiatric Disorder Treatment: Innovations in Drug Design and Targeted Therapy - Kadiri, Sunil Kumar; Rout, Saroj Kumar; Tiwari, Prashant (Drug Delivery Letters, 2025)
As a major global health problem, neuropsychiatric disorders, including depression, schizophrenia, and bipolar disease, have complex etiologies as well as heterogeneous diagnoses of patient treatment responsiveness. Conventional pharmacotherapy is increasingly the go-to treatment due to its wide utilization, but struggles with a number of symptoms surrounding pain that it can only partially treat because of restrictions in drug phenotype-penetrance and delivery methodologies. All too often, conventional treatments exhibit poor efficacy and side effect profiles, leaving most chronic low back sufferers inadequately treated. Here, we summarize recent breakthroughs on the horizon that could revolutionize the treatment of neuropsychiatric diseases in a review article. We examine the state-of-the-art in drug design and emerging technologies, such as computers and artificial intelligence, which provide tools to pinpoint a specific subset for precision therapy. The review also discusses drug delivery systems, including novel nanoparticle carriers and brain-targeted delivery methods, to enhance the bioavailability and reduce the side effects of the drugs. The authors also discuss the applications of new technologies, such as CRISPR gene editing, for directly correcting disease-causing genes. The purpose of this review is to summarize and synthesize these advances, thereby providing an expansive perspective on neuropsychiatric disorder management in the current context, with pointers towards possible new therapeutic strategies leading to a more precise, patient-targeted treatment approach.
Keywords: brain-targeted therapy